1993
DOI: 10.1210/endo.133.3.8396021
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of N-terminal pro-opiomelanocortin peptides in fetal sheep plasma may contribute to fetal adrenal gland development and the pre-parturient cortisol surge.

Abstract: Parturition in sheep is initiated by a rapid rise in fetal plasma cortisol. There is some controversy as to the exact nature of the drive for this pre-partum cortisol surge and it is thought that factors other than ACTH may act in concert to stimulate the development of the fetal adrenal gland. We have investigated the concentrations of ACTH and other peptides derived from pro-opiomelanocortin (POMC) in the circulation of fetal sheep during the final part of gestation, using specific 2-site immunoradiometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Fassnacht et al (12) noted that NH 2 -terminal proopiomelanocortin (POMC) 1-28 stimulated mitosis in adrenocortical tumor cells (Y-1, NCI-h295) and primary cultures of bovine adrenocortical cells via an ERK-dependent pathway that was associated with decreased steroidogenesis. Elevated levels on NH 2 -terminal POMC-derived peptides have been noted in late-gestation fetal sheep and have been postulated to contribute to fetal adrenal gland development and the prepartum cortisol surge (35). We previously reported that POMC and NH 2 -terminal POMC fragment are elevated in the LTH fetus.…”
Section: Discussionmentioning
confidence: 87%
“…Fassnacht et al (12) noted that NH 2 -terminal proopiomelanocortin (POMC) 1-28 stimulated mitosis in adrenocortical tumor cells (Y-1, NCI-h295) and primary cultures of bovine adrenocortical cells via an ERK-dependent pathway that was associated with decreased steroidogenesis. Elevated levels on NH 2 -terminal POMC-derived peptides have been noted in late-gestation fetal sheep and have been postulated to contribute to fetal adrenal gland development and the prepartum cortisol surge (35). We previously reported that POMC and NH 2 -terminal POMC fragment are elevated in the LTH fetus.…”
Section: Discussionmentioning
confidence: 87%
“…Thus altered adrenal responsiveness probably reflects either low levels of ACTH 1-39 in the circulation of the fetal sheep between days 80-115, as suggested by Wintour et al (1995), or a greater proportion of large-molecular-weight peptides, derived from proopiomelanocortin (POMC), that are inhibitory to the adrenal effects of ACTH (Saphier et al 1993, Jones & Roebuck 1980, Schwartz et al 1995. There is diminished expression of P450 C17 in fetal adrenal tissue at days 80-100 of gestation, but the present studies show that the limitation to upregulation of P450 C17 in late pregnancy is apparently not due to the absence of ACTH-R, and reflects more the inadequate or inappropriate stimulus to the fetal adrenal cortical cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is some further evidence from sheep to support the notion that the processing of pro-γ-MSH can change (Saphier et al 1993). In the sheep, parturition is initiated by a rapid rise in the levels of fetal plasma cortisol, and measurement of fetal ACTH levels showed them to be low during gestation and to increase moderately toward the end of gestation.…”
Section: Other Evidence For the Role Of N-pomc In Adrenal Growthmentioning
confidence: 97%